The relationship between understanding of e-learning with self-directed learning among students / Normala Ismail and Mohamad Kamil Ariff Khalid - Ismail, Normala; Khalid, Mohamad Kamil Ariff (Universiti Teknologi MARA, Perlis, 2020)
The main purpose of this study is to identify the students’ understanding of e-learning and their readiness for self-directed learning. A total of 306 Diploma level students of a various program from three faculties at Universiti Teknologi MARA Pahang Branch, Raub Campus have been surveyed. The data were obtained through questionnaires distributed and analyzed using the Statistical Package for Social Sciences (SPSS) version 23. The findings show that the respondents’ level of understanding of the concept and their responsibility on e-learning is high while their readiness for self directed learning is low. The correlation test results show that there is a significant positive relationship between the respondents’ level of understanding to e-learning and their willingness for self-directed learning but the correlation is weak. The findings also showed that the respondents’ level of education and study grade have a significant difference in their readiness for self-directed learning.